Utilizing 3D printed models to assist in complex pediatric cardiac surgery: an interview with Henry Pinchbeck, Michael Richard and Rafael Guerrero. Issue 4 (October 2017) - Pinchbeck, Henry; Richard, Michael; Guerrero, Rafael
Henry Pinchbeck, Michael Richard and Rafael Guerrero speak to Freya Leask, Publisher. Henry Pinchbeck is the CEO of 3D LifePrints (Liverpool, UK), a 3D technology company supplying 3D printing services to the medical sector including the NHS, private hospitals, universities and medical training centers. It is has a 3D printing facility embedded in the Innovation Hub at Alder Hey Children's Hospital (Liverpool, UK). One of the main services is the provision of high quality 3D printed anatomical models from patient data to assist surgeons in planning their procedures, discussing the treatment with their patients and for training and simulation purposes. Michael Richard is 3D LifePrints' Head of Engineering and has previously worked on 3D LifePrints' humanitarian projects in South Africa and Kenya. Mr Rafael Guerrero is a Consultant Pediatric Cardiac Surgeon, Chief of Cardiac Surgery at Alder Hey Children's Hospital and the Director of Cardiac Services in the North West of England. To learn more about how 3D LifePrints supports surgeons at Alder Hey Children's Hospital, visit 3DMedNet to watch a series of video interviews with Henry, Michael and Rafael.